Uji Residu Herbisida Glifosat terhadap Beberapa Imago Parasitoid di Laboratorium - Monalisa Natalia Ambarita; Suzanna Fitriany; Fatimah Zahara (Jurnal Agroekoteknologi, 2015)
The aim of the research was to determine the effect of glyphosate herbicide application on the percentage of live and survive parasitoid age in laboratory and the best time for the introduction of parasitoids to the field after application of parasitoids. The research was held at Laboratory of Sugarcane Research and Developmnet Sei Semayang, Binjai, Medan, North Sumatera from Juny to August 2014. The method used Non-factorial Randomized Complete Design which is application time factor glyphosate herbicide control, 3, 5,7,and 9 days after application respectively.The results showed that giving of herbicides significantly affect mortality Sturmiopsis inferens and Trichogramma spp. Giving herbicides also significantly affected age survive Cotesia flavipes, S. inferens. and Trichogramma spp.Keywords : parasitoid, Cotesia flavipes, Sturmiopsis. inferens, Trichogramma spp., glyphosate herbicide